Assessment of the Mandibular Incisive Canal by Panoramic Radiograph and Cone-Beam Computed Tomography - Ricardo Raitz; Elisabeth Shimura; Israel Chilvarquer; Marlene Fenyo-Pereira (Hindawi Limited, 2014)
Objectives. The region between mental foramens is considered as a zone of choice for implants. However, complications may arise due to an extension anterior to the mental foramen that forms the mandible incisive canal [MIC]. Our goal is to evaluate identification of MIC by both panoramic radiograph [PAN] and cone-beam computed tomography [CBCT]. Methods. 150 cases with bilateral MIC were analyzed. Images of a radiolucent canal, within the trabecular bone, surrounded by a radiopaque cortical bone representing the canal walls, and extending to the anterior portion beyond the mental foramen, were considered by two independent radiologists as being images of MIC. PAN and CBCT of these cases were evaluated by 2 other radiologists at different times. Agreement between results of examination methods was assessed by the Kappa coefficient. The interexaminer and intramethod rates for detection of MIC were analyzed by the McNemar test. Gender, mandible side, examiner, and type of method were analyzed by the generalized estimating equations [GEE] model. Results. significant difference between examiners [PAN:  P=0.146; CBCT: P=0.749] was not observed. Analysis by GEE model showed no significant difference between genders [P=0.411] and examiners [P=0.183]. However, significant difference was observed for identification in both mandible right side [P=0.001], where the identification frequency was higher, and CBCT method [P<0.001]. Conclusions. PAN was not shown to be a safe examination to identify MIC. CBCT should always be used in preoperative planning and to reduce the number of complications in implant surgeries.